2017
DOI: 10.1097/dad.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Apocrine Carcinoma With an In Situ Component and Histiocytoid and Signet-Ring Cells

Abstract: We present a case of cutaneous apocrine carcinoma arising in the axilla of a 71-year-old man. The tumor had a significant component of histiocytoid and signet-ring cells as well as in situ carcinoma within the apocrine glands. The cells expressed GATA3, gross cystic disease fluid protein 15, androgen receptor, and E-cadherin. Estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 were negative. Clinical correlation was required to rule out a metastasis from the breast or the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, our study indicated that lymph node metastasis is seen more frequently in axillary SRCHC cases than in eyelid SRCHC cases [8/11 (73%) versus 1/4 (25%)], even though eyelid SRCHC cases had larger tumours in our study. A literature review also revealed the predominance of axillary SRCHC [10/14 (71%) versus 8/43 (19%)] 2,3,5–7,14–51,54,55 . Distant metastasis was seen in approximately half of both axillary and eyelid SRCHC cases [5/11 (45%) versus 2/4 (50%)].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, our study indicated that lymph node metastasis is seen more frequently in axillary SRCHC cases than in eyelid SRCHC cases [8/11 (73%) versus 1/4 (25%)], even though eyelid SRCHC cases had larger tumours in our study. A literature review also revealed the predominance of axillary SRCHC [10/14 (71%) versus 8/43 (19%)] 2,3,5–7,14–51,54,55 . Distant metastasis was seen in approximately half of both axillary and eyelid SRCHC cases [5/11 (45%) versus 2/4 (50%)].…”
Section: Discussionmentioning
confidence: 98%
“…These were similar to those for conventional AC 52,53 . There were no SRCHC cases located in areas other than the axilla and eyelid 2,3,5–7,14–51,54,55 . Thus, metastasis should be considered for cases arising at other sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastases have occurred in around half of the reported cases, usually to nearby lymph nodes [2,12]. Tumor-related deaths have also been described [6,13,18,19]. The periorbital lesions often present as diffuse swelling and thickening of the involved lid, with normal or erythematous skin, and tend to infiltrate circumferentially around the eyelid, leading to their "monocle-like" appearance [20].…”
Section: Introductionmentioning
confidence: 99%